Hi, i have been reading a mathematical indcution book and i start answering the exercises but i think i have a problem with this one, I'll be grateful if you help
Determine Un if we know that U1=1 and Uk=Uk-1 + 3. for K>1.
suggestion: U1=3*1 - 2, U2=3*2 - 2
I found the solution to this problem on my book, i just need one more thing, the solution on the book is:
1° - the hypothesis is valid for N=1
2° - with Uk = 3k-2
Uk+1 = Uk + 3 = 3k - 2 + 3 = 3(k+1) - 2 //This is the solution
I just want someone explain me why Uk+1 is equal to Uk + 3 especially why that three.
thanks for your help.